2010
DOI: 10.1007/s12032-010-9434-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrative and oxidative DNA damage as potential survival biomarkers for nasopharyngeal carcinoma

Abstract: Currently, there are no satisfactory biomarkers available to screen for nasopharyngeal carcinoma (NPC). Nitric oxide (NO), produced by inducible nitric oxide synthase (iNOS), has been suggested to cause nitrative and oxidative stress, leading to the accumulation of 8-nitroguanine (8-NitroG) and 8-hydroxy-2'-deoxyguanosine (8-OHdG) and the subsequent transversion mutation of DNA. The aim of this study was to evaluate iNOS expression and the status of nitrative and oxidative stress in NPC. Fifty-nine cases of NP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 47 publications
(44 reference statements)
2
33
0
1
Order By: Relevance
“…IL-6 was expressed mainly in inflammatory cells of nasopharyngeal tissues of EBV-infected patients. We also found that serum levels of 8-oxodG were significantly higher in NPC patients than control subjects (Huang et al, 2011). Collectively, these findings indicate that the nuclear accumulation of EGFR and activation of STAT3 by IL-6 play a key role in iNOS expression and resultant DNA damage, leading to EBV-related NPC.…”
Section: Epstein-barr Virus and Nasopharyngeal Carcinomasupporting
confidence: 51%
See 1 more Smart Citation
“…IL-6 was expressed mainly in inflammatory cells of nasopharyngeal tissues of EBV-infected patients. We also found that serum levels of 8-oxodG were significantly higher in NPC patients than control subjects (Huang et al, 2011). Collectively, these findings indicate that the nuclear accumulation of EGFR and activation of STAT3 by IL-6 play a key role in iNOS expression and resultant DNA damage, leading to EBV-related NPC.…”
Section: Epstein-barr Virus and Nasopharyngeal Carcinomasupporting
confidence: 51%
“…Using biopsy and surgical specimens of nasopharyngeal tissues from NPC patients in southern China, we performed double immunofluorescent staining to examine the formation of 8-nitroguanine and 8-oxodG Huang et al, 2011). Intensive immunoreactivity of iNOS was detected in the cytoplasm of 8-nitroguanine-positive cancer cells.…”
Section: Epstein-barr Virus and Nasopharyngeal Carcinomamentioning
confidence: 99%
“…There is a causal link between oxidative stress and cancer, where ROS produced by transformed epithelial cells and activated stromal and inflammatory cells account for DNA damage and genomic instability (3,6,31,32) and further contribute to carcinogenesis. Hence, we assessed accumulation of superoxide anions by staining freshly frozen bladder sections with dihydroethidine (DHE), whose oxidation gives rise to the fluorescent derivative ethidene (31,33).…”
Section: Bladders Of Sparc -/-Mice Show Enhanced Accumulation Of Rosmentioning
confidence: 99%
“…8-Nitroguanine and 8-oxodG were formed in epithelial cells of EBV-positive patients with chronic nasopharyngitis, and their intensities were significantly stronger in cancer cells of NPC patients [57]. The serum level of 8-oxodG in NPC patients was significantly higher than control patients, suggesting the involvement of oxidative stress [58]. We confirmed EBV infection at the nasopharyngeal tissues by using in situ hybridization for EBV-encoded RNAs (EBERs).…”
Section: Epstein-barr Virus and Nasopharyngeal Carcinomamentioning
confidence: 59%